In vitro physicochemical and biological properties of titanium alloy, zirconia, polyetheretherketone, and carbon fiber-reinforced polyetheretherketone - Su, Jingjing; Xing, Xiaojie; Lin, Yanjun; Gao, Yuerong; Xing, Yifeng; Xu, Zhiqiang; Chen, Jiang (Frontiers in Materials, 2022)
Implant repair is a common means to restore the normal function of the hard tissues (bone or teeth). At present, the commonly and potentially used implant materials include titanium alloy (Ti), zirconia (Zr), polyetheretherketone (PEEK), and 30% carbon fiber reinforced PEEK (CFR-PEEK). This study compares their physicochemical and biological properties, including surface morphology, contact angle, nano hardness, elastic modulus, and the impact on the proliferation and osteogenic differentiation of bone marrow mesenchyml stem cell. Additionally, the differences in bacteria adhesion rates among materials were compared. CFR-PEEK had the highest contact angle, followed by PEEK, Zr, and Ti. Zr had the highest nano hardness and modulus of elasticity, followed by Ti, CRF-PEEK, and PEEK. There was no statistically significant difference in cytotoxicity among materials based on the liquid extract test. However, the relative cell proliferation rate on the surface of CFR-PEEK was slightly lower than that of Ti and Zr. Moreover, alkaline phosphatase activity, extracellular matrix mineralization, and osteogenic gene expression with the Ti and Zr materials were higher than with the PEEK and CFR-PEEK materials at Day 7, and Zr showed the highest osteogenic gene expression level among materials at Day 14. Ti had the greatest number of bacterial colonies that adhered to it, followed by Zr, CFR-PEEK, and PEEK. While the mechanical properties of PEEK and CFR-PEEK were closer to bone tissue and their anti-adhesion effect against bacteria was better than those of Ti and Zr, modification methods are needed to improve the osteogenic properties of these biopolymers.